Factors Influencing Mothers' Quality of Sleep during Their Infants' NICU Hospitalization. Issue 5 (3rd September 2022) - Lebel, Valérie; Feeley, Nancy; Robins, Stephanie; Stremler, Robyn
ABSTRACT: Study Objectives: The purpose of this study is to identify factors associated with Neonatal Intensive Care Unit (NICU) mothers' quality of sleep as measured with the General Sleep Disturbance Scale (GSDS). Methods: Recruitment took place in a level 3 NICU. At enrollment, mothers completed a socio-demographic questionnaire, described their presence in the unit and their breast milk expression behavior. They also completed online or paper questionnaires about NICU-related stress, symptoms of postpartum depression, family-centered care, perception of noise and light in the unit, and sleep disturbances. Data regarding the infant's clinical condition were collected from their medical file. Pearson correlations were performed to identify associations between mothers' quality of sleep and other study variables. Subsequently, to compare mothers with a clinically significant GSDS score to mothers with a non-significant score, a binary logistic regression model was conducted. Results: 132 mothers participated. Sleep disturbances of mothers with an infant hospitalized in the NICU was positively correlated with stress ( r = 0.40; p = .00), depressive symptoms ( r = 0.51; p = .00), and breast milk expression ( r = 0.23; p = .01). In addition, for mothers with significant levels of depressive symptoms (OR = 1.19; p = .00), with greater presence in the unit (OR = 1.36; p = .04), or with other children at home (OR = 3.12; p = .04), the likelihood of clinically significant sleep disturbances was increased. Conclusions: These results improve our understanding of the factors influencing the quality of sleep of mothers whose premature infant is hospitalized for 2 weeks or more in the NICU. In addition, these results allow the identification of mothers having a higher possibility for sleep disturbance, which enables the implementation of targeted interventions to promote adequate sleep.